The ways of improving the effectiveness of state programs as a part of performance management in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
The article deals with the ways of improving the efficiency of government programs as part of a result-oriented management of the Republic of Kazakhstan. If say specifically, according to the new system of state planning which was adopted in 2007, changes in the budgetary system and the system of state planning improve budgeting process, government spending and increase the effectiveness of the new programs. The budgeting oriented to the results is a basis of it. After above mentioned program which was adopted in 2007, in 2010 was adopted the new rules of assessment of state programs and strategic planning. As a result of this, the number of the programs were reduced and left only the most important and useful of them. Instead of them, they include strategic plans of government agencies. All which mentioned above give an opportunity to increase the efficiency of state administration.
Keywords: a new system of state planning; budgeting; results-oriented; government programs; effectiveness of state administration